2015
DOI: 10.1111/imr.12371
|View full text |Cite
|
Sign up to set email alerts
|

The potential role of retroviruses in autoimmunity

Abstract: In the last 20 years research in Immunology underwent fundamental changes. Most importantly, the identification of the key role of innate immune pattern recognition receptors (PRRs) that recognize evolutionarily conserved molecular patterns on infectious pathogens. This results in priming of innate immune cells, which in turn activate and direct the adaptive immune response. Progress in innate immune recognition instigated the current working hypothesis, that recognition of endogenous ligands by PRRs results i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 137 publications
0
21
0
1
Order By: Relevance
“…For instance, overexpression of ERV envelope proteins, as seen in the brain of patients affected with some neurodegenerative and autoimmune disorders, can induce a wide range of cellular processes and abnormalities associated with these pathologies, such as neurodegeneration 127 , autoinflammation 128 , demyelination 129 , and superantigen activity 130 . Furthermore, the cytoplasmic accumulation of nucleic acids derived from activated TEs, including double-stranded RNA, reverse transcribed cDNA, or RNA–DNA hybrids, are increasingly regarded as potent immunological ‘adjuvants’ that may trigger autoimmune responses 131,132 and other toxicities when present in elevated quantities 133,134 .…”
Section: Pathogenic Effects Of Te Regulatory Activitiesmentioning
confidence: 99%
“…For instance, overexpression of ERV envelope proteins, as seen in the brain of patients affected with some neurodegenerative and autoimmune disorders, can induce a wide range of cellular processes and abnormalities associated with these pathologies, such as neurodegeneration 127 , autoinflammation 128 , demyelination 129 , and superantigen activity 130 . Furthermore, the cytoplasmic accumulation of nucleic acids derived from activated TEs, including double-stranded RNA, reverse transcribed cDNA, or RNA–DNA hybrids, are increasingly regarded as potent immunological ‘adjuvants’ that may trigger autoimmune responses 131,132 and other toxicities when present in elevated quantities 133,134 .…”
Section: Pathogenic Effects Of Te Regulatory Activitiesmentioning
confidence: 99%
“…HERVs are remnants of viral infections of the primate germline millions of years ago, which have been transmitted to their progeny. Tens of HERV families have been described, representing 8% of the human genome -few of which have been associated with several autoimmune diseases such as systemic lupus erythematous, rheumatoid arthritis, MS, amyotrophic lateral sclerosis, and Sjögren's syndrome (13,24,(46)(47)(48). In particular, the HERV-W family has been involved in the pathogenesis of MS through its envelope protein HERV-W-Env, also known as MSRV-Env (23)(24)(25).…”
Section: Discussionmentioning
confidence: 99%
“…Despite decades of research, no causative link between viral infections and T1D pathogenesis has been confirmed (6). A new type of pathogenic element is emerging in the etiology of autoimmune diseases, the human endogenous retroviruses (HERVs), which are remnants of ancient viral infections that occurred millions of years ago (13). HERVs were generated by a process called endogenization, which happened when environmental retroviruses infected the germinal cells of hosts during evolution, leading to their transmission into Human endogenous retroviruses (HERVs), remnants of ancestral viral genomic insertions, are known to represent 8% of the human genome and are associated with several pathologies.…”
Section: Introductionmentioning
confidence: 99%
“…The resultant DNA is later integrated into host DNA through viral integrase enzyme. Viral-integrated DNA (proviral DNA) is translated and transcribed to proteins as part of host genome using the genetic machinery of infected cell 1-3 . …”
Section: Introductionmentioning
confidence: 99%